Decision Making for Insurance Eligibility based on Mortality Differential in Southeast Asian Countries (Universitas Ahmad Dahlan, 2022)
Indonesia, Malaysia, and Singapore are each at different stages of economic development, all have achieved sufficient size and economic strength that they are being prospected by several global life insurance and life annuities. Their economies have speedily been moving out of their traditional agrarian bases and becoming far more urbanized and industrialized. This study aims to compare the characteristics of various mortality risk factors between three countries in Southeast Asia (Indonesia, Malaysia, and Singapore) and analyze differences in mortality rates for the development of the life insurance business